2023
DOI: 10.3390/polym15153210
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Accelerated Deterioration of High-Temperature Vulcanized Silicone Rubber under Multi-Factor Aging Tests Considering Temperature Cycling

Abstract: High-temperature vulcanized silicone rubber (HTV-SR) employed for composite insulators is continuously subjected to a complex environment of alternating heat, corona discharge, humidity, etc. These stresses (especially alternating heat) complicate the aging mechanism of HTV-SR, which lacks systematic investigation. In this paper, a multi-factor aging platform considering temperature cycling, moisture, and corona discharge is established. Specifically, four temperature-cycling settings are employed, each of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…(1) We have studied the mechanical and dielectric properties of silicone rubber materials used in cable accessories under high-temperature shielding materials [5]. This does not apply to the actual conditions where the cable runs under power frequency voltage for a long time and may withstand operating overvoltage and lightning overvoltage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(1) We have studied the mechanical and dielectric properties of silicone rubber materials used in cable accessories under high-temperature shielding materials [5]. This does not apply to the actual conditions where the cable runs under power frequency voltage for a long time and may withstand operating overvoltage and lightning overvoltage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li Shuzhen et al have developed a silicone rubber aging test method that takes into account temperature cycling. They have summarized the effects of temperature cycling on the aging mechanism and behavior of silicone rubber, and confirmed that temperature cycling can lead to the fatigue failure of silicone rubber material [18]. Zhang Zhongyuan et al utilized scanning electron microscopy and Fourier transform infrared spectroscopy to analyze the degradation mechanism of the silicone rubber sheath on the surface of composite crossarms under the individual effects of different aging factors.…”
Section: Introductionmentioning
confidence: 99%